Serum level of laminin in rats fed with a high-fat diet with sulodexide administration - O. G. Gileva; E. G. Butolin; M. V. Tereshchenko (Бюллетень сибирской медицины, 2022)
Background. Increased consumption of animal fat with food contributes to the accumulation of lipids both in the blood and in individual cell structures. Excess fat initiates oxidative stress reactions, which may result in a violation of the structural and functional integrity of cells, in particular, hepatocytes and endotheliocytes. Cytolysis may release specific liver enzymes and activate synthesis of extracellular matrix components, one of the markers of which is a non-collagen glycoprotein laminin.The drug sulodexide, having a pronounced angioprotective, hypolipidemic, and fibrinolytic effects, contributes to restoration of a number of metabolic disorders.Aim. To study the content of lipid metabolism parameters, major enzymes of hepatic cytolysis, and laminin in the blood of rats fed with a high-fat diet against the background of sulodexide administration.Materials and methods. For the study, outbred rats were selected, which were divided into three groups – two experimental groups and one control group. The rats of the first and second experimental groups were fed with a diet with a high content of animal fat (44% of the daily calorie content) for 35 days. In addition, the rats of the second experimental group were daily subcutaneously injected with sulodexide at a dose of 8.5 LRU / kg in terms of the animal’s body weight for 35 days. Starting from day 36 of the experiment, the rats of the control group, as well as the rats of the two experimental groups were fed with a standard diet of the vivarium. The animals were decapitated and blood was taken on day 21, 35, and 60 of the experiment. In the blood serum, the levels of the main lipid metabolism parameters, specific liver enzymes, and laminin were determined.Results. An increase in the body weight of animals and the level of the studied lipid metabolism parameters in the blood serum was revealed. It is likely that the structural integrity of hepatocytes was affected with the release of liver enzymes into the bloodstream and an increase in their content in the blood of rats. In addition, synthesis of extracellular matrix components was activated with an increase in the serum level of laminin, which performs important structural and regulatory functions.Conclusion. The use of sulodexide had a favorable effect on the studied metabolic disorders caused by a high-fat diet. It resulted in the normalization of the synthesis of laminin, one of the major non-collagen proteins of the extracellular matrix.